1999
DOI: 10.1094/pdis.1999.83.10.944
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Resistance to Rhizoctonia Limb Rot in a Core Collection of Peanut Germ Plasm

Abstract: Diseases caused by Rhizoctonia solani lead to significant reductions in peanut yields and quality throughout the world. A subset of accessions from the peanut germ plasm core collection plus the commercial cultivars Florunner, Southern Runner, Georgia Browne, and Georgia Green were evaluated for resistance to limb and seedling hypocotyl infections caused by R. solani. Georgia Green and core accessions 95 (PI 497351), 197 (PI 331326), 208 (PI 274193), 244 (PI 343361), 246 (PI 343398), and 524 (PI 288178) had le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 24 publications
1
40
0
Order By: Relevance
“…The core collection is comprised of 831 entries selected at random (1%), at random by country of origin (26%), and by multivariate clustering of phenotypic descriptor information (73%) to minimize repetitiveness in the collection while representing the collection's genetic diversity (16,18). The peanut core collection has been previously evaluated for resistance to tomato spotted wilt virus (TSWV), Rhizoctonia limb rot, late leaf spot, peanut root knot nematode, preharvest aflatoxin contamination, early leaf spot, and Cylindrocladium black rot (2,13,16,17,19). To our knowledge, the core collection has not been previously evaluated for reaction to Sclerotinia blight.…”
mentioning
confidence: 99%
“…The core collection is comprised of 831 entries selected at random (1%), at random by country of origin (26%), and by multivariate clustering of phenotypic descriptor information (73%) to minimize repetitiveness in the collection while representing the collection's genetic diversity (16,18). The peanut core collection has been previously evaluated for resistance to tomato spotted wilt virus (TSWV), Rhizoctonia limb rot, late leaf spot, peanut root knot nematode, preharvest aflatoxin contamination, early leaf spot, and Cylindrocladium black rot (2,13,16,17,19). To our knowledge, the core collection has not been previously evaluated for reaction to Sclerotinia blight.…”
mentioning
confidence: 99%
“…Hence screening of various germplasm sets, such as core and mini core collection accessions, is important for the identification of resistant sources. Previous researchers have demonstrated that valuable genes in germplasm collections can be effectively identified by using a core or mini core collection (Anderson et al 1996a;Franke et al 1999;Holbrook and Anderson 1995;Holbrook et al 2000a;Isleib et al 1995). Mini core germplasm accessions have been widely screened in several crops, including groundnut, for identifying resistant sources to different biotic (Kusuma et al 2007) and abiotic stresses (Vadez et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Isleib et al, 1995Isleib et al, 1995Hammond et al, 1997Holbrook et al, 2000a,b Holbrook,1997Holbrook et al, 1998Holbrook et al, 1997Franke et al, 1999Anderson et al, 1996 Reference Table 5. Germplasm evaluations for the peanutcore collection.…”
Section: Evaluation Of the Core Collection Theorymentioning
confidence: 99%